Case Report: Severe rash/desquamation induced by sorafenib in an uHCC patient and its clinical management - Lin, Yan; Liu, Ping-Yu (Frontiers in Pharmacology, 2022)
Background: Sorafenib-related dermatological toxicity is a well-known adverse reaction that could severely affect therapeutic outcomes. Rash/desquamation is one of the common clinical presentations among its variable manifestations. Currently, no standard continuum of care for sorafenib-related rash/desquamation has been established. Case summary: A 75-year-old woman with colorectal cancer who developed unresectable hepatocellular carcinoma (uHCC) six years later received sorafenib 400 mg twice daily. She developed grade 3 Common Terminology Criteria for Adverse Events (CTCEA) rash and bullae on lower extremities bilaterally after 2 weeks of sorafenib use. Rash and blisters began to show up on the left calf and were then merged as large bullae full of liquid and spread to both lower extremities. The bullae then erupted and skin began to slough off, which affected patient’s normal daily function. To lessen the condition, sorafenib was stopped permanently, and dexamethasone intravenous (IV) infusion at 5 mg daily for 3 days and piperacillin/tazobactam were used. The skin became dried without exudate or ulcerations after a month. Conclusion: For severe (CTCAE Grade 3 or above) sorafenib-related rash/desquamation, short-term corticosteroid pulse therapy with large dose is usually effective besides routine skin care, and antibiotic can be considered if infection is present. Permanent cessation of sorafenib should be considered if severe manifestations, such as erythema multiforme (EM) and Steven-Johnson syndrome (SJS), are suspected.